IMPLEMENTATION OF REGIONAL REGULATION NUMBER 24 OF 2014 CONCERNING THE IMPLEMENTATION OF SOCIAL WELFARE IN LAMPUNG PROVINCE - Arya Anasta Adam S; Baharuddin; Anggalana (Constitutional Law Society, 2022)
Society is one of the focuses of the study of state administration, where there are a lot of complexities of social problems and needs in it. In dealing with any existing problems, of course, it must start from the formulation of all forms of policies carried out by the government with related elements. This article will discuss how the implementation of Regional Regulation Number 24 of 2014 concerning the Implementation of Social Welfare in Lampung Province and what are the inhibiting factors and supporting factors of implementation in the implementation of social welfare in Lampung Province. The research method used in this article uses a normative approach and an empirical approach. The inhibiting factor for the Regional Regulation Number 24 of 2014 concerning the Implementation of Social Welfare in Lampung Province lies in the lack of understanding of the people who do not understand the regulations regarding social welfare so that people always assume that the government is not doing its function properly.